An Examination of the Severity of Periodontal Disease in Elderly Men with Varying Degrees of Physical Activity - Smitha Shetty; Smeet Gusani; Mranali K Shetty (Institute of Medico-legal Publications Pvt Ltd, 2022)
Abstract Objectives: Regular physical activity has been shown to protect against chronic diseases instudies. The majority of studies have only looked at this association in children and teenagers. The goalof our study was to see how regular physical activity affected elderly males.Methods: The study comprised 90 male patients aged 50 to 69 who visited the A. B. Shetty MemorialInstitute of Dental Sciences’ outpatient department.Results: The prevalence of localized periodontitis was highest among the medium physical activitygroup and prevalence of generalized periodontits was highest among low physical activity group.Conclusions: Our findings reveal that regardless of the patients’ levels of physical activity, they alldeveloped periodontitis, which was linked to their brushing habits.